Characterization of the consumer of agri-food products in traditional markets against covid-19 in Ecuador - Rodríguez Ulcuango, Olga Maritza; Guerra Rodríguez, Cristian Oswaldo; Trujillo Chávez, Hugo Santiago; Rodríguez Ulcuango, Carlos Iván (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020DO - 10.36779/mktdescubre.v1iEspecial.590, 2021)
When shopping before the health emergency, the food and essential products that were sold in popular markets presented a position in the consumer's mind by tradition and by price. But, the big question is, Has the health crisis influenced the consumption of agri-food products in traditional markets? To answer this hypothesis, a methodology was designed under a quali-quantitative approach in a descriptive study, under the survey technique directed at the economically active population of the city of Riobamba, where it was identified that the behavior is in accordance with the level of income and the fear of contagion with Covid-19. During the health emergency, food companies and supermarkets have benefited from this health crisis, as they comply with biosecurity protocols, providing confidence and changing consumer behavior in Ecuador; However, this has significantly affected traditional and popular markets, since they were not prepared for the effect caused by the pandemic. By not immersing in the path of innovation or the absence of a vaccine, the existing risks will be in the sale in these places, therefore the characterization will continue to vary significantly.